Strategic Brand Positioning Through Cultural Event Programming at Garuda Wisnu Kencana Cultural Park - Tjiadarma, Erica Pricilla; Zaim, Ilma Aulia (Graduate Program Magister Manajemen Pendidikan, 2025)
This study examines cultural event programming as a strategy to strengthen brand positioning at Garuda Wisnu Kencana (GWK) Cultural Park in the domestic market. A mixed-methods approach was used, combining interviews with four internal stakeholders and surveys of 400 domestic visitors (2022–2025). The analysis applied Cai’s brand positioning model, McKercher and du Cros’s cultural tourist typology, and Getz and Morrison’s participatory event framework. Findings show that while GWK is widely recognized, its cultural image is narrowly associated with the iconic statue, and the visitor experience is often perceived as static. A misalignment between GWK’s cultural mission and commercial focus further weakens its cultural appeal. This study proposes a repositioning model based on symbolic narrative integration, participatory cultural programs, and targeted visitor segmentation. The findings contribute to cultural tourism by introducing an integrated branding-programming model that emphasizes internal alignment to deliver more authentic and immersive cultural experiences.